Review of Promitzer et al. (eds), Health, Hygiene and Eugenics in Southeastern Europe to 1945 - Kritsotaki, Despo (Historein, 2013)
Review of: Christian Promitzer, Sevasti Trubeta and Marius Turda (eds), Health, Hygiene and Eugenics in Southeastern Europe to 1945, Budapest: Central European UP, 2011. 440 pp.